Comparison of clinical results of anteromedial and transtibial femoral tunnel drilling in ACL reconstruction - Leena Metso (BMC Musculoskeletal Disorders, 2020)
Abstract Background A femoral bone tunnel in ACL reconstruction can be constructed from the outside in or from the inside out. When doing it inside out, the approach can be via the anteromedial (AM) portal or through the tibial bone tunnel. It has been suggested that better results might be expected by doing it anteromedially. Clinical results after femoral tunnel drilling via the AM or transtibial (TT) techniques in reconstruction of anterior cruciate ligament (ACL) are presented. Methods Three hundred patients with ACL injuries were chosen for this study from previously collected data on ACL reconstructions. They were divided into two groups: 150 patients treated with AM drilling and 150 treated with TT drilling. In the AM group, the reconstructions were performed using a semitendinosus graft with the Tape Locking Screw (TLS™) technique (n = 87) or Retrobutton™ femoral and BioScrew™ tibial fixation with a semitendinosus-gracilis graft (n = 63). In the TT group, the fixation method used was Rigidfix™ femoral and Intrafix tibial fixation with a semitendinosus-gracilis graft. The evaluation methods were clinical examination, knee scores (Lysholm, Tegner and IKDC) and instrumented laxity measurements (KT-2000™). Our aim was to evaluate if there was better rotational stability and therefore better clinical results when using AM drilling compared to TT drilling. Results After excluding revision ACL reconstructions, there were 132 patients in the AM group and 133 in the TT group for evaluation. At the 2-year follow-up, there were 60 patients in the AM group (45.5%) and 58 in the TT group (43.6%). There were no statistically significant differences between the groups in any of the evaluation methods used. Conclusion Both drilling techniques resulted in improved patient performance and satisfaction. We found no data supporting the hypothesis that the AM drilling technique provides better rotational stability to the knee. Trial registration ISRCTN registry with study ID ISRCTN16407730 . Retrospectively registered Jan 9th 2020.